Pengaruh Motivasi Terhadap Kinerja Tenaga Kesehatan di Puskesmas Sinjai Barat Kabupaten Sinjai - Andi Armayudi Syam; Andi Ahmad Malikul Afdal (Kolaborasi : Jurnal Administrasi Publik, 2023)
The study's goal was to determine how motivation affected the performance of healthcare professionals at the Tengngalembang Community Health Centre in the West Sinjai Subdistrict of the Sinjai District. In terms of the research methodology, a quantitative approach was utilised, along with a descriptive research design and methods for gathering data through questionnaires and observation. In addition to pulling the sample using saturation sampling approach, there were 35 nurses and midwives in the health centre of Tengngalembang Community West Sinjai Subdistrict of Sinjai district who were all included in this study. The findings demonstrate that motivation is the end result of a variety of internal and external processes that lead to the development of passion and perseverance in carrying out particular tasks. The results of the study show the influence of motivation on the performance of health workers in the health centre of Tengngalembang community in Sinjai subdistrict west of Sinjai district. The motivation variable can have a positive influence on the performance of health workers in the Tengngalembang community health centre in Sinjai subdistrict.